Apo, Zn2+-bound and Mn2+-bound structures reveal ligand-binding properties of SitA from the pathogen Staphylococcus pseudintermedius. Issue 6 (24th November 2014) - Abate, Francesca; Malito, Enrico; Cozzi, Roberta; Lo Surdo, Paola; Maione, Domenico; Bottomley, Matthew J.
Abstract : The Gram-positive bacterium Staphylococcus pseudintermedius is a leading cause of canine bacterial pyoderma, resulting in worldwide morbidity in dogs. S. pseudintermedius also causes life-threatening human infections. Furthermore, methicillin-resistant S. pseudintermedius is emerging, resembling the human health threat of methicillin-resistant Staphylococcus aureus . Therefore it is increasingly important to characterize targets for intervention strategies to counteract S. pseudintermedius infections. Here we used biophysical methods, mutagenesis, and X-ray crystallography, to define the ligand-binding properties and structure of SitA, an S. pseudintermedius surface lipoprotein. SitA was strongly and specifically stabilized by Mn 2+ and Zn 2+ ions. Crystal structures of SitA complexed with Mn 2+ and Zn 2+ revealed a canonical class III solute-binding protein with the metal cation bound in a cavity between N- and C-terminal lobes. Unexpectedly, one crystal contained both apo- and holo-forms of SitA, revealing a large side-chain reorientation of His 64, and associated structural differences accompanying ligand binding. Such conformational changes may regulate fruitful engagement of the cognate ABC (ATP-binding cassette) transporter system (SitBC) required for metal uptake. These results provide the first detailed characterization and mechanistic insights for a potential therapeutic target of the major canine pathogen S. pseudintermedius, and also shed light on homologous structures in related staphylococcal pathogens afflicting humans.